Rare genetic skeletal disorders: Evolving terminology, therapies, education and advocacy - Laura L. Tosi, MD (Elsevier, 2024)
In the US, rare diseases are defined as disorders affecting fewer than 200,000 US residents or disorders for which there is no reasonable expectation that drug development costs will be recoverable by US sales. Almost 800 of the approximately 10,000 defined rare diseases are bone disorders. Until recently, their rarity and heterogeneity have unfortunately hindered their exploration at both clinical and scientific levels. However, wider availability of genetic testing, development of new surgical and pharmaceutical treatment options, and patient advocacy have motivated efforts to study, diagnose, and treat these disorders. Thus, care of the patient with a rare skeletal disorder is now evolving rapidly. This report presents a brief summary of important developments in skeletal disorders impacting bone quality and frequently co-managed by pediatric orthopaedic surgeons. Key Concepts: (1) Although a "cure" is not yet available for most rare bone disease patients, new agents are frequently being advanced as new genes and their products are identified as molecules to target. (2) Medical therapies, often combined with surgical interventions and physical therapy, are reducing pain and increasing function in many pediatric orthopaedic patients with rare bone disorders. (3) New tools for physician education and patient management are increasingly available to assist the pediatric orthopaedic surgery community.